2018
DOI: 10.5539/gjhs.v10n8p55
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Serum Il-6 Changes as Proliferative Cytokines in Patients With Nasopharyngeal Carcinoma Before and After the Ionizing Radiotherapy

Abstract: Background: Nasopharyngeal carcinoma is a squamous cell malignancy derived from the nasopharyngeal epithelial layer. This study aimed to calculate the IL-6 levels in patients with nasopharyngeal carcinoma before and after radiotherapy, in the week I and week 3 during the radiotherapy, and 2 weeks after the radiotherapy. Methods:The study was conducted in a prospective cohort on 16 people suffering from nasopharyngeal carcinoma and undergoing radiotherapy, i.e. 9 patients were in stage I of nasopharyngeal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The results of previous showed different results. Kadir et al [25] in cohort study of 16 NPC patients also found that IL-6 levels were not affected by histopathology type. In other hand, Elhabashy [26] explained there was a correlation between NPC, IL-6 and EBV.…”
Section: Advances In Health Sciences Research Volume 46mentioning
confidence: 87%
“…The results of previous showed different results. Kadir et al [25] in cohort study of 16 NPC patients also found that IL-6 levels were not affected by histopathology type. In other hand, Elhabashy [26] explained there was a correlation between NPC, IL-6 and EBV.…”
Section: Advances In Health Sciences Research Volume 46mentioning
confidence: 87%
“…However, local recurrence and distant metastasis are still the leading causes of death among NPC patients [ 6 ]. Chronic inflammation participates in the development, recurrence, and metastasis of malignant tumors, and is one of the important characteristics of NPC [ 7 , 8 , 9 , 10 ]. In the tumor microenvironment, chronic inflammation can induce the enrichment of inflammatory factors and promotes tumor recurrence, chemotherapy resistance, angiogenesis, invasion, and metastasis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The target of radiotherapy is to damage the DNA in the nucleus of carcinoma cells which will result in damage or decreased ability to proliferate. As described above, the majority of NPC patients are diagnosed at an advanced stage, this causes 85% of the sufferers to die (Kadir, Retnowati, Akil, & Usman, 2018). Despite advances in radiotherapy, the presence of metastases in NPC is the cause of radiotherapy failure.…”
Section: Introductionmentioning
confidence: 99%